Imagem e memória: arqueologia da imagem nas aulas de Artes Visuais do Instituto Federal do Maranhão – campus Buriticupu - Oliveira, Régis Costa de (2016)
The imagistic reading in visual arts classes, usually occurs from a Eurocentric tradition acquis which is strange to much of the student visuality and the curatorial process intermediated by the teacher. Given these characteristics, it is imperative to think of new methodological procedures for the practice of reading images. Thus, this article analyzes the application of the project Image and Memory in Visual Arts classes at the Federal Institute of Maranhão, Buriticupu campus to the practice of imagistic reading from the curatorial model present at the Mnemosyne Atlas by Aby Warburg and the archeology image recommended in the studies of Georges Didi-Huberman, in order to place the student as the protagonist of the curation process visual information, from his visuality and weaving the threads that articulate images from mnemonics and conceptual aspects.